TANTANGAN DAN HAMBATAN PENGUSAHA AKOMODASI LOKAL DALAM MENGELOLA ONLINE TRAVEL AGENT DI NUSA PENIDA - Darsana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023), 2023)
The purpose of this study to find out marketing with online travel agents used by local accommodation entrepreneurs on Nusa Penida Island and how local entrepreneurs manage these OTAs to increase the existence of their accommodation businesses. Entrepreneurs did not understand how to manage online travel agent, such as a lack of concern for maintaining the system and price disparity rates and the lack of ability to carry out innovative promotions through OTA, as well as dependence on offline travel agents. The theory of marketing and OTA have used in this researched, data obtained through interviews and analyzed using qualitative descriptive methods. Research results show thatLocal accommodation entrepreneurs need to increase their network or partners in promoting the accommodation business by registering their property business with online travel agents other than Booking.com and Agoda and actively managing accommodation marketing in maintaining their accommodation business.